Transforming coffee from an empirical beverage to a targeted nutritional intervention: health effects of coffee's core functional components on chronic diseases - Peng, Rui; Lan, Mengqi; Zhang, Yifei; Zhang, Shishi; Yu, Beibei; Yang, Xu; Li, Shiming; Liu, Zhenhua; Kang, Wenyi (Frontiers in Nutrition, 2025)
As one of the most widely consumed beverages worldwide, coffee has garnered increasing scientific interest due to its potential health benefit in recent decades. Epidemiological studies have consistently shown that regular coffee consumption significantly reduces the incidence risks of various chronic diseases, including type 2 diabetes mellitus (T2DM), Alzheimer's disease (AD), cardiovascular disorders, and nephropathies. Pharmacological research further supports these findings, linking the protective effects of coffee to its complex composition of bioactive compounds. Coffee beans contain over 1,000 such compounds, with caffeine, trigonelline, chlorogenic acids (CGAs), cafestol, kahweol, and melanoidins constituting the core functional components. These phytochemicals act through multi-target, synergistic mechanisms that regulate neurological functions, metabolic homeostasis, and inflammatory pathways. This review systematically explores the major bioactive constituents of coffee, focusing on the molecular mechanisms underlying four key biological activities associated with chronic disease prevention: neuroprotection, anti-diabetic/anti-obesity effects, antioxidant activity, and anti-inflammatory properties. By elucidating these pharmacological pathways, we aim to establish a molecular theoretical foundation for repositioning coffee from an empirical beverage into a targeted nutritional intervention agent.